Environmental factors inducing gastric cancer: insights into risk and prevention strategies - Puyi He; Xiaomei Li; Dan Zou; Futian Tang; Hao chen; Yumin Li (Discover Oncology)
Abstract Gastric cancer, a prevalent malignant tumor worldwide, poses a significant challenge to global health. Despite ongoing advancements in treatment methods, its high incidence and mortality rates remain concerning. Although progress in treating gastric cancer is encouraging, a more critical focus is on enhancing prevention efforts. Understanding the risk factors associated with gastric cancer is crucial for its prevention. This article summarizes the environmental factors related to the development of gastric cancer and their prevention, including: Living or working environment factors (air pollution, water quality, soil pollution, radiation, altitude, climate), dietary habits (meat, high-fat diet, high-salt diet), lifestyle habits (smoking, Drinking, sleep, coffee), and viral and bacterial exposures (Epstein-Barr virus, Human cytomegalovirus, Helicobacter pylori). Additionally, the article discusses current research directions and aims to provide a reference for researchers, paving the way for future preventive and therapeutic strategies.